Genesis and Distribution of Low Fluvial Terraces Formed by Holocene Climate Pulses in Brazil - Perez Filho, Archimedes (2022)
Low fluvial terraces present azonal spatialization, encompassing several geomorphological compartments and climate zones in Brazil. Their genesis is directly related to river dynamics. When influenced by allogenic forces, such as Holocene climate pulses, it results in channel incision and posterior abandonment of the floodplain. Relatively plain landforms at different altimetric levels identified between the current floodplain and hillslope (low river terraces) are a result of these processes. Previous works using Optically Stimulated Luminescence (OSL) in low terraces of several rivers in Brazil have indicated morpho-chronologic similarities between depositional events, raising the hypothesis of feedbacks and fluvial adjustments relatively simultaneous to Holocene climate events. Considering these dynamics, this study employed OSL to obtain absolute dating information for 114 samples taken from distinct levels of the low river terraces of 30 rivers in Brazil, integrating the database of the IG-UNICAMP laboratory of Geomorphology and Environmental Analysis. Based on the data and statistical analysis (cluster and correlation analysis), this study aimed to identify relationships between different variables which might have controlled spatial homogenous and heterogeneous feedbacks during distinct paleoenvironmental contexts. The proposed methodology tested a fundamental hypothesis of the regional climatic geomorphology, and the results obtained may contribute to future discussions on the relationship between low river terraces and anthropic occupation.